Mesh Sutured Repairs of Abdominal Wall Defects. Issue 9 (September 2016) - Lanier, Steven T.; Dumanian, Gregory A.; Jordan, Sumanas W.; Miller, Kyle R.; Ali, Nada A.; Stock, Stuart R.
Abstract : Background: A new closure technique is introduced, which uses strips of macroporous polypropylene mesh as a suture for closure of abdominal wall defects due to failures of standard sutures and difficulties with planar meshes. Methods: Strips of macroporous polypropylene mesh of 2 cm width were passed through the abdominal wall and tied as simple interrupted sutures. The surgical technique and surgical outcomes are presented. Results: One hundred and seven patients underwent a mesh sutured abdominal wall closure. Seventy-six patients had preoperative hernias, and the mean hernia width by CT scan for those with scans was 9.1 cm. Forty-nine surgical fields were clean-contaminated, contaminated, or dirty. Five patients had infections within the first 30 days. Only one knot was removed as an office procedure. Mean follow-up at 234 days revealed 4 recurrent hernias. Conclusions: Mesh sutured repairs reliably appose tissue under tension using concepts of force distribution and resistance to suture pull-through. The technique reduces the amount of foreign material required in comparison to sheet meshes, and avoids the shortcomings of monofilament sutures. Mesh sutured closures seem to be tolerant of bacterial contamination with low hernia recurrence rates and have replaced our routine use of mesh sheets and bioprosthetic grafts. Abstract : Supplemental Digital Content is available in the text.